Aspectos reproductivos de Prochilodus nigricans, en comunidades Wampis del medio morona, provincia Datem del Marañón, Loreto – Perú - Chumpi Ugkum, Estacio (2025)
The present investigation aimed to determine the reproductive characteristics of the "boquichico" (Prochilodus nigricans) in the middle basin of the Morona River, under the jurisdiction of the Wampis Autonomous Territorial Government, specifically in the fishing areas near the community of Caballito. The study was carried out between October and November 2022, recording a total of 412 individuals, of which 288 (69.90%) were females and 124 (30.10%) males. A methodology based on landing records and direct observations of the gonads over a period of 12 months, in the early hours of the morning, was used. In addition, biometric data (standard length, fork length, total length, and weight) were collected for both sexes. The results obtained revealed that Prochilodus nigricans has a sex ratio of 1.6:1 in favor of females and reaches the average size of sexual maturity at 25.42 cm total length. The gonadosomatic index (GSI) indicated greater reproductive activity between November and January, with a peak in January (14.40%), followed by a progressive decline until August. Histological analysis showed continuous presence of mature gonads (stage IV), with final development (stage V) concentrated in March and April. The average absolute fecundity was 202,484.2 oocytes per female, and the condition factor was 2.3 in females and 2.4 in males, with seasonal variations related to river level.